Happy marriage?! 05 - Enjoji, Maki (Viz Media, 2014)
Chiwa Takanashi has married a total stranger, company president Hokuto Mamiya, to get her father out of debt. Rather than having her husband continue to support her feckless father, Chiwa accepts a job at Shinjo Sakuraba's startup without telling Hokuto. Will Chiwa and Hokuto's newfound wedded bliss last now that she's working alongside her crush from college?